Pengaruh jumlah Cr2O3 terhadap kelemasan kulit atasan sepatu dari kulit biawak finish natural - Muchtar Lutfie; Widhiati Widhiati; Esti Rahayu (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1996)
The study is aimed at detecting the amount of Cr2O3 in percent added in the tanning of lizard skins for natural finished shoe upper leather. The materials used in this study are 36 pieces of dry preservated lizard skins which are tanned to natural finished shoe upper leather, while the tanning agent used are Cr2O3 that added in veried amount as 0,5 %; 1,0 %; 1,5 % and 15 % Basyntan DLX. Using varian’s analysis, it is found that there is a significant difference in the softness of the leather caused by the amount of Cr2O3 added. The use of 1,5% Cr2O3 obviously shows the best result. INTISARI Penelitian ini bertujuan untuk mengetahui jumlah Cr2O3 (%) yang digunakan pada penyamakan kulit biawak untuk kulit atasan sepatu finish natural. Dengan menggunakan 36 lembar kulit biawak yang diawet kering diproses untuk kulit jadi untuk kulit atasan sepatu dengan finish natural. Bahan penyamak yang digunakan adalah Cr2O3 dengan variasi 0,5 %; 1,0 %, 1,5 % serta 15 % Basyntan DLX. Dengan menggunakan analisa varias’s ternyata didapatkan ada beda sangat nyata kelemasan akibat pengaruh perbedaan jumlah Cr2O3 yang diberikan. Penggunaan 1,5 % Cr2O3 adalah jumlah yang terbaik.